Assessing creativity : strategies and tools to support teaching and learning in architecture and design : final report 2012. - Williams, Anthony; Askland, Hedda Haugen (Office for Learning and Teaching, 2012)
Report of an investigation into the question of creativity in design. The authors describe a growing concern in the Australian architecture and design community about the difference between universities' understanding of architectural professional knowledge and the skills actually required to practise in the field. The following issues facing architecture and design educators have been identified: a lack of understanding of the pedagogical dimensions of creativity in design; a lack of appropriate strategies to understand where different levels of creativity occur and how they should be assessed; and, a lack of appropriate models and tools to support assessment of creative works. Closely related to these problems is the lack of an unambiguous disciplinary definition of creativity, as well as an assumed relationship between creativity and design. This report provides an analysis and evaluation of (i) the architecture and design community's understanding of creativity, (ii) the role of creativity in design education and, more specifically, (iii) how creativity is assessed, and (iv) how this assessment is framed through the mechanisms of quality assurance and the needs of accountability. [Executive summary, ed]